KEPEMIMPINAN STRATEGIS MENGHADAPI ANCAMAN NIR-MILITER; DI TENGAH PANDEMI COVID-19 DALAM PERTAHANAN NIR-MILITER - Pramudita Wardani; Sobar Sutisna; Makmur Supriyatno (DAS Institute, 2022)
The emergence of the 21st century is characterized by rapid changes in human life, both in terms of behavior and thinking. In reality, change is the certainty of a constantly evolving era. Indonesia can face a non-military threat; therefore, it needs leaders who think strategically. Strategic leadership is an action that can create harmonization between the demands of the organization’s external environment (the world) with the vision, mission, strategy, and organization. The world, especially Indonesia, is currently in Covid-19 or Coronavirus Disease 19 pandemic. As of January 21, 2022, 340,543,962 confirmed cases and 5,570,163 deaths were reported worldwide. While in Indonesia, 4,280,248 cases and 144,201 deaths have been determined, this number has increased since the emergence of Covid-19. The National Defense System is all form of effort to prevent, overcome and fend off opponents, protect and defend national interests from things that endanger state sovereignty, the territorial integrity of the Republic of Indonesia, and the safety of the entire nations as well as all kinds of coercion with violence and attacks both military and non-military from others